PENGARUH PENGGUNAAN MEDIA INTERAKTIF DISERTAI LKS TERHADAP HASIL BELAJAR IPA PADA KELAS IX SMP - Siska Angreni (Scientiae Educatia: Jurnal Pendidikan Sains, 2017)
The research was aimed to reveal the difference between learning achievement of the students involving taught by using media interactive Compact Disk (CD) media and worksheet and interactive compact disk (CD) media and those taught by using conventional media. This was a quasi-experiment research. The population of this research was class IX of SMP Negeri 5 Kerinci. The researcher then chose class IXC as the experimental class I taught by using interactive CD media with a worksheet, class IXD as the experimental class II taught by using media interactive CD media, and class IXE as the control class taught by using conventional method. The data it was analyzed by using One Way ANOVA and Post hoc Tukey HSD. The results of One Way ANOVA test is Fcalculated (13,76)>Ftable (3,45). Based on the hypothesis acceptance criteria, if Fcalculated >Ftable, HI was accepted. After analyzing the data by using Way ANOVA, the data then was tested by using Post hoc Tukey HSD, and the result were: the result of te study suggested taught by using media interactive Compact Disk (CD) media and worksheet and interactive compact disk (CD) media had significant effect on the learning outcome, which means media interactive Compact Disk (CD) media and worksheet and interactive compact disk (CD) media had positive effect on the biology learning outcome.Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar peserta didik dengan menggunakan media CD interaktif disertai LKS dan media CD interaktif. Jenis penelitian adalah eksperimen semu. Sampel penelitian siswa kelas IXC sebagai eksperimen I, sedangkan siswa kelas IXD sebagai eksperimen II dan siswa kelas IXE sebagai kontrol Analisis data menggunakan uji Anova satu arah dan dilanjutkan dengan uji lanjutan (Post hoc) Tuket HSD. Hasil penelitian uji Anova Satu Arah adalah hasil belajar  Fhitung (13,76) > Ftabel (3,45). Berdasarkan kriteria penerimaan hipotesis jika Fhitung > Ftabel, maka H1 diterima. Dengan demikian dapat disimpulkan bahwa penggunaan media Compact Disk (CD) interaktif disertai LKS memberikan pengaruh yang signifikan terhadap hasil belajar, artinya penggunaan media Compact Disk (CD) interaktif disertai LKS berpengaruh positif terhadap hasil belajar Biologi.